Impact of Global Value Chain and Industrial Agglomeration on China’s Automobile Industry Upgrading - TingTing, Sun (Sun Tingting, 2025)
The automobile industry is a crucial component of China's national economy, serving as both a pillar and a leading sector. In the era of globalization, the trend of mergers and acquisitions has swept across the globe, making China's automobile industry a microcosm of the global automotive landscape. This industry is characterized by its high degree of interconnectedness, an extensive industrial chain, and a broad employment scope, all of which play a significant role in driving the growth of the national economy. Although China leads the world in automobile production, the Chinese automobile industry lacks competitiveness in the international market. The objective of this study is to investigate the factors influencing the upgrading of China's automobile industry and provide recommendations to enhance its competitiveness in the global market. Specifically, this thesis mainly studies the impact of industrial agglomeration and global value chain on the upgrading of China's automobile industry, and discusses whether government support plays a moderating role in the process of industrial agglomeration's impact on the upgrading of China's automobile industry, and whether foreign direct investment plays a moderating role in the process of global value chain's impact on the upgrading of China's automobile industry. Moreover, it analyses whether technological innovation plays a mediating role in the impact of global value chain on the upgrading of China's automobile industry. Finally, it examines whether human capital has a threshold effect in the impact of industrial agglomeration on the upgrading of China's automobile industry. It aims to contribute to the development of China's automobile industry and strengthen China's position in the global automobile market. This study selects a 21-year dataset from 28 provinces in China, spanning from 2000 to 2020, to ensure the availability and authenticity of the data. To measure industrial upgrading, total factor productivity (TFP) is chosen as the proxy variable. The TFP is calculated using the DEA-Malmquist method with the Deap2.1 software. For estimation, System GMM and the dynamic panel threshold model are employed, with regression analysis conducted using Stata 17 software. The empirical results indicate that industrial agglomeration positively promotes the upgrading of China's automobile industry. However, embedding in the global value chain inhibits this upgrading. Government support does play a mediating role in the influence of industrial agglomeration on the upgrading of China's automobile industry. Similarly, foreign direct investment moderates the impact of global value chain on the upgrading of China's automobile industry, and technological innovation serves as a mediating factor in the effect of global value chain on the upgrading of China's automobile industry. Additionally, human capital acts as a threshold factor influencing the impact of industrial agglomeration on the upgrading of China's automobile industry, with a threshold value of 8.5099. Specifically, when human capital is below this threshold, industrial agglomeration does not significantly promote the upgrading of the industry. It is only when human capital exceeds the threshold that industrial agglomeration significantly enhances the upgrading of China's automobile industry. Based on these empirical analysis results, this study proposes recommendations for the upgrading of China's automobile industry.